Persepsi Mahasiswa Teknik Informatika Terhadap Perkuliahan Daring Sebagai Sarana Pembelajaran Selama Pandemi Covid-19 - Ita Aristia Sa’ida; Sahri Sahri; Mula Agung Barata (Departement of Mathematics Education, 2023)
With the COVID-19 pandemic, universities in Bojonegoro Regency, especially Nahdlatul Ulama Sunan Giri University, are conducting online lectures. In the implementation of learning, it is different from conventional lectures so that the use of learning models determines the effectiveness of online lectures during the COVID-19 period. This study examines the perceptions of Informatics Engineering students' learning models through approaches to the use of learning media in online lectures, learning communication models, learning styles, and the effectiveness of online lectures. This research is specifically for Informatics Engineering students whose learning is not only limited to delivering material but needs to be carried out in practicum both in the laboratory and in the field. Along with the online learning process, some material that should have been carried out by research had to not be carried out. Given these obstacles, student perceptions regarding the effectiveness of online lectures that lead to learning models with learning media approaches, communication models, learning styles among Informatics Engineering students in Bojonegoro Regency determine the success of this learning process. With this, researchers examine the perceptions of Informatics Engineering students towards online lectures during the COVID-19 pandemic. This research was conducted to determine student perceptions of online learning. This research uses Descriptive Analysis, namely to examine the perceptions of Informatics Engineering students regarding online learning models during the COVID-19 pandemic. Which online learning model can be known through several approaches, such as online learning media, learning communication models, learning styles and the effectiveness of online learning. Data obtained from observations in the form of giving online questionnaires. The samples involved were Informatics Engineering students at Nahdlatul Ulama University Sunan Giri Bojonegoro as respondents in this study. The output targeted in this study is Sinta 4 indexed National Journal Publications with research TKT 3.